Analisis Kinerja Waralaba Laundry Menggunakan Metode Performance Prism - Harits, Dimaz; Hasyim Tuankotta, Muhamad; Nurdin, Ishak (SURYA TEKNIKA, 2026)
Holistic measurement of a company’s performance is essential to ensure the quality of its performance and its sustainability. This study measures the performance of PT. XYZ using the 5 dimensions of the Performance Prism—namely strategy, process, capability, contribution, and stakeholder needs—integrated with the OMAX and Traffic Light System. A total of 47 KPIs were identified across 5 stakeholder groups, including customers, employees, suppliers, the government, franchisees, and owners. The measurement results show that PT. XYZ’s performance score is 6.385, which is categorized as “good,” with 5 KPIs classified as green (good) and 42 classified as yellow (fair). The results of this study also indicate the level of importance of each KPI, allowing performance improvements to be prioritized based on the company’s priorities